Optimal layout of offshore wind farms - Kyaw, Tun Min. (2012)
The objective of this project was to do a literature search for the wind characteristics especially in wind speed and direction to determine the optimal layout of wind farm producing the maximum energy. The project was reviewed on the background of wind turbines, and types of wind turbines whether it was HAWT or VAWT. Moreover main components of a wind turbine system, the wind characteristic and the power in the wind were studied. The average power in the wind was also found by using wind power probability density functions such as Weibull probability density function and Rayleigh distribution function. Then, the layout of an offshore wind farm was carried out by taking into consideration of wind turbine spacing, wind speed, wake effects and power curve of the wind turbine generator to maximize the wind power. Moreover, different layout of wind farm power to grid connection had been discussed including offshore collector system, substation and transmission to shore. Lastly, the optimization of maximum power, optimization of power control and offshore substructure’s foundation were carried out in the last chapter.